A basis set superposition error‐free second‐order perturbation theory from Hermitian chemical Hamiltonian approach self‐consistent field canonic orbitals. Issue 8 (26th July 2021) - Salvador, Pedro; Mayer, István
Abstract: We present an alternative perturbational approach free of basis set superposition error (BSSE) within the framework of the chemical Hamiltonian approach (CHA). The new formulation (CHA‐S‐MP2) is based on canonic (and orthogonal) CHA orbitals obtained from a hermitized CHA Fock operator. The final expression shows a considerable simplification of the method as compared to the previous CHA‐MP2 formalism. Numerical full geometry optimizations of water and hydrogen fluoride dimers and potential energy surfaces for helium and argon dimers for several basis sets are presented. The present method is compared to both the counterpoise and previous CHA‐MP2 BSSE correction schemes, showing a remarkable agreement between all three methods. However, the wrong behavior using the aug‐cc‐pVDZ basis set indicates that the present method is not as robust as the original non‐hermitian CHA‐MP2 formulation. Abstract : A new basis‐set superposition error‐free perturbational treatment is explored (CHA‐S‐MP2), based on canonic and orthogonal orbitals obtained from a hermitized Fock operator in the context of István Mayer's CHA. The final expression shows a considerable simplification of the method as compared to the previous CHA‐MP2 formalism, although it is less robust.